CGRP-dependent molecular signaling drives bone marrow stem cell osteogenesis in distraction osteogenesis - Hamiti, Yimurang; Liu, Kai; Wang, Sulong; Yang, Xin; Kadier, Xiriaili; Yusufu, Aihemaitijiang (Frontiers in Bioengineering and Biotechnology, 2025)
Distraction osteogenesis (DO) represents a promising approach for treating large bone defects, yet prolonged consolidation periods limit clinical efficacy, and the molecular mechanisms underlying neuropeptide regulation of bone regeneration remain poorly understood. We systematically investigated calcitonin gene-related peptide (CGRP)-dependent molecular signaling effects on rat bone marrow mesenchymal stem cells (BMSCs) through comprehensive in vitro analyses and evaluated therapeutic efficacy in a rat femoral DO model (n = 108). CGRP (10−8 M) significantly enhanced BMSC proliferation, migration, and osteogenic differentiation while reducing apoptosis by 47%. Molecular analysis revealed rapid cyclic adenosine monophosphate (cAMP) elevation (2.3-fold within 30 min) and subsequent PKA/CREB pathway activation, upregulating key osteogenic genes (Runx2, Sp7, Spp1, and Bglap). The CGRP receptor antagonist and the PKA inhibitor completely abolished these effects, confirming pathway dependence. In vivo, local CGRP treatment accelerated bone formation, improving bone mineral density (1.8-fold), trabecular microarchitecture, and biomechanical properties, including ultimate load (89% increase) and stiffness (76% increase), compared to controls. These findings demonstrate that CGRP-dependent molecular signaling drives bone marrow stem cell osteogenesis through cAMP/PKA/CREB activation, providing mechanistic insights into neuropeptide regulation of bone regeneration and identifying CGRP as a promising therapeutic target for optimizing distraction osteogenesis outcomes.